2019
DOI: 10.7554/elife.48660
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic cell-cycle entry and cell-state-dependent fate outputs of injury-reactivated tectal radial glia in zebrafish

Abstract: Gliosis defined as reactive changes of resident glia is the primary response of the central nervous system (CNS) to trauma. The proliferation and fate controls of injury-reactivated glia are essential but remain largely unexplored. In zebrafish optic tectum, we found that stab injury drove a subset of radial glia (RG) into the cell cycle, and surprisingly, proliferative RG responding to sequential injuries of the same site were distinct but overlapping, which was in agreement with stochastic cell-cycle entry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…5A,B). Similarly, recent sc-RNAseq studies in the adult zebrafish brain with higher cell throughput, only identified cells with transcriptomic profiles of radial glia as proliferating neurogenic precursors (Cosacak et al, 2019;Yu and He, 2019). Our findingsthat a subset of zebrafish RG corresponds to intermediate neurogenic progenitors, the major proliferating and amplifying population from the postnatal and adult murine hippocampus, while a NBN.1 subset corresponds to neuroblast, their direct progenysupport this view.…”
Section: Discussionsupporting
confidence: 80%
“…5A,B). Similarly, recent sc-RNAseq studies in the adult zebrafish brain with higher cell throughput, only identified cells with transcriptomic profiles of radial glia as proliferating neurogenic precursors (Cosacak et al, 2019;Yu and He, 2019). Our findingsthat a subset of zebrafish RG corresponds to intermediate neurogenic progenitors, the major proliferating and amplifying population from the postnatal and adult murine hippocampus, while a NBN.1 subset corresponds to neuroblast, their direct progenysupport this view.…”
Section: Discussionsupporting
confidence: 80%
“…To examine macrophage responses after injury, we performed immunostaining using an IB4 antibody conjugated with Dylight 594 (Lai et al, 2017) in the intact and injured optic tectum at 6, 12, and 24 hpi (Figures 2A-D and Supplementary Figure 2). Few IB4-positive cells were observed in the intact optic tectum (Figures 2A,E), suggesting that IB4-positive cells were not microglia as there were fewer of these cells in the intact optic tectum than GFP-positive cells in Tg(mpeg1:GFP) (Lindsey et al, 2019;Yu and He, 2019). Interestingly, we found that there were significantly more IB4-positive cells in the injured hemisphere than in the uninjured hemisphere at 6, 12, and 24 hpi.…”
Section: Stab Wound Injury Induced Macrophage Migration and Rg Proliferation In The Adult Optic Tectum Within 24 Hmentioning
confidence: 80%
“…At 6 hpi, the number of proliferative RG cells in the two hemispheres of the optic tectum did not significantly differ (Figure 1E); however, significant RG proliferation was observed on the injured side at 12 hpi in comparison to the contralateral uninjured hemisphere. Furthermore, the number of BLBP-PCNA+ cells, which likely include immune cells such as microglia and macrophages (Lindsey et al, 2019;Yu and He, 2019), also significantly increased from 12 to 24 hpi (Figure 1F). To examine macrophage responses after injury, we performed immunostaining using an IB4 antibody conjugated with Dylight 594 (Lai et al, 2017) in the intact and injured optic tectum at 6, 12, and 24 hpi (Figures 2A-D and Supplementary Figure 2).…”
Section: Stab Wound Injury Induced Macrophage Migration and Rg Proliferation In The Adult Optic Tectum Within 24 Hmentioning
confidence: 95%
See 2 more Smart Citations